2020
DOI: 10.1152/advan.00121.2019
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of self-regulated learning skills: the roles of tutors and students

Abstract: Problem-based learning (PBL) is an instructional method that offers students the opportunity to develop self-regulatory strategies as an explicit learning outcome. As a multifaceted PBL environment, the guidance of tutors is important to students as they develop self-regulatory learning (SRL) skills and self-efficacy, the most focused motivational element in SRL. The present study examines the relationship between academic achievement and PBL self-efficacy levels, as well as the role played by tutors. A cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
1
24
0
3
Order By: Relevance
“…Most of the research articles revealed many advantages of SDL. Self-assessment, identifying skills, and confidence-building were the major advantages cited (1,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Various methods, such as problem-based learning, flipped classroom, and case-based learning, helped students work on themselves to gain knowledge, and analyze and interpret it with critical thinking, and also apply it leading to a definite diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the research articles revealed many advantages of SDL. Self-assessment, identifying skills, and confidence-building were the major advantages cited (1,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Various methods, such as problem-based learning, flipped classroom, and case-based learning, helped students work on themselves to gain knowledge, and analyze and interpret it with critical thinking, and also apply it leading to a definite diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…All members were not actively contributing (13,16,18,23). Organizational skills were also absent (20,22). SDL was effective in the simple topic; however, complex topic learning was a big challenge, especially in learning surgical skills (13,20,26).…”
Section: Discussionmentioning
confidence: 99%
“…2 Consequently, educational models emphasizing critical thinking, lifelong learning skills, and effective communication and teamwork, in the form of collaborative and active learning, are being incorporated into medical curricula. 3,4 Problem-based learning (PBL) and team-based learning (TBL) are prime examples of such 'studentcentered' and collaborative active learning strategies. In PBL, real-life clinical scenarios are introduced to students in small groups.…”
Section: Introductionmentioning
confidence: 99%
“…PBL has several advantages over the more traditional lecture-based courses: an integrated knowledge base, exposure to real-life experience at an earlier stage in the curriculum, etc [7]. The current study showed that the majority of the students were positive that PBL integrates basic and clinical Knowledge and increases the ability to deal with authentic problems of patients.…”
Section: Discussionmentioning
confidence: 59%